The Effect of Discussion-Based Learning to Improve TOEFL ICT’S Score - Lutfiah; Hidayat, Akhmad Nuris (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2026)
improving students’ TOEFL ICT scores at Universitas dr. Soebandi. The research employed a quantitative approach using a quasi-experimental design. The population of this study consisted of university students, while the sample was selected through purposive sampling from two second-semester Pharmacy classes, namely Class 23A and Class 23B, with a total of 60 students. Class 23A was assigned as the experimental group and taught using Discussion-Based Learning, while Class 23B served as the control group and was taught using the conventional lecture method. Data were collected through TOEFL pre-test and post-test instruments adapted from Barron’s TOEFL, 6th Edition by Pamela J. Sharpe. The data were analysed using the Independent Sample T-Test through SPSS. The findings showed that the average pre-test scores of the experimental and control groups were relatively similar, namely 382 and 379, indicating comparable initial ability. After the treatment, the post-test results revealed that the experimental group achieved an average score of 437, while the control group obtained 405. The score improvement of the experimental group (+55) was higher than that of the control group (+26). Statistical analysis showed that the significance value (Sig. 2-tailed) was 0.014, which was lower than 0.05, and the t-count value (3.32) was higher than the t-table value (2.00). Therefore, the null hypothesis was rejected and the alternative hypothesis was accepted. It can be concluded that Discussion-Based Learning had a significant positive effect on improving students’ TOEFL ICT scores.